Synthesis and Enhanced Electromagnetic Wave Absorption Properties of Fe3O4@ZnO Mesoporous Spheres. Issue 1663 (15th April 2014) - Sun, Danping; Jiang, Wei; Wang, Yanping; Sun, Chen; Zou, Quan; Liu, Gongzong; Liu, Jie; Li, Fengsheng
ABSTRACT: Mesoporous Fe3 O4 nanoparticles coated with ZnO nanocrystals were successfully synthesized by a simple solution method at low temperature. The transmission electron microscopy analysis indicates that the mesoporous Fe3 O4 nanoparticles are monodispersed with a mean diameter of 160 nm and the thickness of ZnO layer is 15 nm approximately. The porosity of the products was further substantiated by the nitrogen (N2 ) sorption measurement. The N2 adsorption-desorption isotherm curve can be identified as type IV, which is a characteristic of mesopores. Electromagnetic (EM) wave absorption properties of the as-prepared Fe3 O4 @ZnO mesoporous spheres-wax composites were investigated at a room temperature in the frequency range of 0.5∼18 GHz. Interestingly, the Fe3 O4 @ZnO mesoporous spheres exhibit an enhanced EM wave absorption due to the mesoporous structure. The multiple absorbing mechanisms result from the interface polarization induced by the special core/shell and mesoporous structures as well as dipole polarization of both Fe3 O4 and ZnO. The results demonstrate that the Fe3 O4 @ZnO mesoporous spheres are attractive candidates for a new kind of EM wave absorption materials with wide absorption frequency band.